School Dropout Among Children and It's Implication(s): Perspectives from Rural Ghana - Wiafe, Ernestina (My University, 2023)
Early marriage in boys contrary to the happenings in Namberg in the Jirapa district, the fact that female children's early marriage is due to religious practices came as a surprise finding. Available field data by Abotsi et al. (2018) revealed dropout rates were higher for youngsters between the ages of 6 and 10 than for those between 11 and 15, with 63.4 percent being males (p. 8). These statistics reveal boy-child education is not what it portrays to be in Ghana and has been left to its fate. While advocacy for the girl-child and vulnerable members of the Ghanaian community is on the ascendancy and that which the researcher admires, supports, and advocates for, the total neglect or continuous inadequate support for boys' education is an effect that will come to hit hard on us as a nation and a global community because we refused to ensure educational equity. Frantic efforts by all stakeholders to at least sustain educating boys while improving girls' education and opportunities will be a needed balance to avoid the reverse effect and perceived consequences, which might call for advocacy for boy-child education in the near future. Hostile school environment due to excessive corporal punishment was identified as a major reason given by schoolchildren in the communities for dropping out of school. This is unfortunate! If education accepted in Ghanaian society as a panacea for poverty alleviation has its major players, with the teacher and school authorities the reason students in these communities leave school, then we are failing as a people in this noble profession called to nurture lives for the common good of society. Because we have parts to play as teachers, research such as this must be made available, and reforms addressing the issues must be included in professional development to help keep everyone abreast of happenings in the sector while finding the best practices to mitigate recurrence. The researcher is of the view authorities can correct recalcitrant students and still keep them in school. Generally, findings from the document analysis show similarities in the dropout phenomenon across the selected rural communities of Ghana. The researcher is of the impression school dropout issues might be extremely difficult to understand because of the various factors contributing to them. Further studies and interventions, both structural and systemic, are highly recommended. Ghana is one of 54 countries in Africa, located in the west and south of the Sahara. This sovereign nation is geographically 92,000 square miles, or about 239,460 square kilometers. In all, three rural school communities in two regions of Ghana were the focus of the study. The communities are (1) the Asutifi school district in the Brong-Ahafo region, (2) the Nchiraa Circuit in the Wenchi Municipal Assembly in Brong-Ahafo, and (3) Jarapa Municipal (Nambeg) in the Upper West region of Ghana.
Keywords: School dropout; Rural Ghana; Early Marriage; Teenage Pregnancy